Transcription-inducing activity of natural and synthetic juvenile hormone agonists through the Drosophila Methoprene-tolerant protein. - Yokoi, T.; Nabe, T.; Ishizuka, C.; Hayashi, K.; Ito-Harashima, S.; Yagi, T.; Nakagawa, Y.; Miyagawa, H. (Pest Management Science, 2020)
Juvenile hormones (JHs) are a class of sesquiterpenoids that play a pivotal role in insect growth and reproduction. Synthetic JH agonists (JHAs), including pyriproxyfen, have been widely used as insecticides to control agricultural pests and disease vectors. The antimetamorphic action of JHAs is mediated by their intracellular receptor, the heterodimer of Methoprene-tolerant (Met) and Taiman (Tai) proteins. Although a range of bioassay systems has been developed to detect the activity of JHAs, each of these systems has its own drawback(s), such as poor reproducibility, the use of radioactive ligands or the effect of endogenous JH-signaling factors. To address these issues, we constructed a new luciferase reporter assay for JHAs in mammalian HEK293T cells transiently transfected with the Drosophila Met and Tai genes. This reporter system gave highly reproducible results and showed nanomolar sensitivity to natural JHs. We then applied this reporter system to a structure-activity relationship (SAR) analysis of 14 natural and synthetic JHAs, leading to identification of the ligand structural factors important for the transcription-inducing activity. Because this reporter system is not affected by the signaling cascade downstream of the JH receptors, it is suitable for evaluating the intrinsic activity of JHAs. The SAR results obtained in this study therefore provide invaluable information on the rational design of novel JHA insecticides.